Narrative and gender as mutually constituted meaning-making systems. (19th August 2022) - Fivush, Robyn; Grysman, Azriel
Abstract: Both gender and narrative are foundational to the ways in which humans engage in meaning-making. Arguing from evolutionary, psychological and feminist theoretical perspectives, we posit that narratives and gender are culturally mediated mutually constituted meaning-making systems: Narratives are defined through gender and gender is defined through narrative. To contextualise this argument, we define 'narrative' and 'gender' and review the extant literature on how gender is expressed in culturally mediated master narratives and how narratives are performed differently by women and men. Our core argument is that the very act of narrating is a gendered activity that constructs, represents and narrates gender as a primary category of human existence, and these fundamentally gendered ways of narrating then construct, define and reify gendered ways of being in the world.